2015
DOI: 10.1371/journal.pone.0145536
|View full text |Cite
|
Sign up to set email alerts
|

Virological Response and Antiretroviral Drug Resistance Emerging during Antiretroviral Therapy at Three Treatment Centers in Uganda

Abstract: BackgroundWith the scale-up of antiretroviral therapy (ART), monitoring programme performance is needed to maximize ART efficacy and limit HIV drug resistance (HIVDR).MethodsWe implemented a WHO HIVDR prospective survey protocol at three treatment centers between 2012 and 2013. Data were abstracted from patient records at ART start (T1) and after 12 months (T2). Genotyping was performed in the HIV pol region at the two time points.ResultsOf the 425 patients enrolled, at T2, 20 (4.7%) had died, 66 (15.5%) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 17 publications
5
42
0
Order By: Relevance
“…On the contrary, in a study in Myanmar, 94% of patients had an undetectable viral load and only 4% had ART failure. It is further reported that 84.7% of respondents on first and second line treatment in the Myanmar study had viral load below 1000 copies/ml [24]. The viral loads in this study support the pill count adherence method as the viral loads depict the adherence level in patients.…”
Section: Respondent's Last Viral Loadsupporting
confidence: 70%
“…On the contrary, in a study in Myanmar, 94% of patients had an undetectable viral load and only 4% had ART failure. It is further reported that 84.7% of respondents on first and second line treatment in the Myanmar study had viral load below 1000 copies/ml [24]. The viral loads in this study support the pill count adherence method as the viral loads depict the adherence level in patients.…”
Section: Respondent's Last Viral Loadsupporting
confidence: 70%
“…However, given that stavudine is no longer being prescribed in Uganda and in most resource‐limited settings in accordance with the WHO ART guidelines , this issue will probably be less of a problem in the future, which is somewhat reassuring. Fortunately, we also found a fairly low prevalence of the K65R mutation (in 11% of individuals with virological failure), which is another NRTI resistance mutation that can confer pan‐NRTI resistance, although one study reported that K65R mutations are likely to increase with increased use of tenofovir as a first‐line option . VL measurement with enhanced adherence counselling has been demonstrated to be effective for individuals who are in the first few years of ART in South Africa .…”
Section: Discussionmentioning
confidence: 70%
“…22,23 The third possibility, which we believe could account for most of the TAMs in the present study is previous undisclosed ART use with undocumented viral failure and drug resistance. This hypothesis is supported by the lower CD4 counts detected in patients with TAMs.…”
Section: Discussionmentioning
confidence: 72%